Answer:
First, we need to solve the equation in the problem for y to put it in slope-intercept form so we can determine its slope:
2y−6x=4
2y−6x+6x=6x+4
2y−0=6x+4
2y=6x+4
2y2=6x+42
2y2=(6x2)+(42)
y=3x+2
The slope-intercept form of a linear equation is: y=mx+b
Where m is the slope and b is the y-intercept value.
Therefore the slope of this equation is m=3
A perpendicular line will have a slope (let's call this slope mp) that is the negative inverse of this line. Or, mp=−1m
Substituting gives:
mp=−13